Polymer Networks with Antibacterial Activity by UV Photopolymerization (2009)
The crosslinking by radical UV photopolymerization of mixtures of acrylic oligomers added with 2,4,40 -trichloro-20 -hydroxydiphenyl ether (TCDPE) allows to obtain polymer films which perform like hygienic coatings. The release of the bioactive compound from two types of acrylic networks obtained by UV crosslinking of polyfunctional monomers, namely, epoxy-based and urethane-based diacrylic oligomers, has been investigated. The photopolymerization process was influenced by biocide presence only at high biocide concentration, where the plasticizing effect of the biocide increased the double bond conversion. The kinetic curve of the photopolymerization was fitted by an Avrami-like equation and the release of TCDPE from the networks into solutions of ethanol–water of different compositions was discussed on the base of the Fick’s diffusion equation. The antimicrobial activity of the UV photopolymerized film has been tested by putting the coatings in contact with two types of colony-forming bacteria, the Escherichia coli (Gram negative) and the Staphylococcus aureus (Gram positive). Strong hygienic performances toward the tested pathogens were observed for the urethane and epoxy films containing TCDPE in quantities as low as 0.1 wt %. VC 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 2334–2342, 2009.